Unibook Per un database sull'UniversitÃ - Rossi, Paolo (Scienze della comunicazione - Open access, 2017)
"The project that inspires this volume is the production and analysis of certain and stabilized data on the university system, in an interpretative framework presented by teachers and researchers who have long been engaged in studies and research on reformism and innovation processes in universities. The collected essays offer a mapping of the University and its various aspects: from system governance to the training programs and funding, from postgraduate training to internationalization, from the evaluation of scientific research to ""Abilitazione Scientifica Nazionale"" and the Third Mission."